Introducing a spread into the Kyle model - Marcus Salomonsson (Stockholm School of Economics, The Economic Research Institute (EFI), 2009)
The Kyle (1985) model is extended to take into account market maker competition and the spread. It is shown that with a spread the Kyle model has a Nash equilibrium also with two market makers, not only with three or more, as shown in earlier research. The spread is endogenized, and two testable predictions of the model are generated. The first is that the spread is increasing in the standard deviation of the fundamentals. The second is that it is independent of the standard deviation of noise trades.
Keywords: D53; D82; G12; G14; 330; market microstructure; spread; market maker; Mikrostrukturanalyse; Wertpapierbörse; Bid-Ask Spread; Asymmetrische Information; Noise Trading; Theorie